2015
DOI: 10.1088/0004-637x/804/2/85
|View full text |Cite
|
Sign up to set email alerts
|

General Relativistic Hydrodynamic Simulation of Accretion Flow From a Stellar Tidal Disruption

Abstract: We study how the matter dispersed when a supermassive black hole tidally disrupts a star joins an accretion flow. Combining a relativistic hydrodynamic simulation of the stellar disruption with a relativistic hydrodynamics simulation of the tidal debris motion, we track such a system until 80% of the stellar mass bound to the black hole has settled into an accretion flow. Shocks near the stellar pericenter and also near the apocenter of the most tightly-bound debris dissipate orbital energy, but only enough to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
410
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 326 publications
(419 citation statements)
references
References 44 publications
(53 reference statements)
7
410
2
Order By: Relevance
“…In obtaining this conclusion one assumes that accretion flows are stationary and driven by local viscosity. It might not apply to flows forming in TDEs (see e.g., Coughlin & Begelman 2014;Shiokawa et al 2015) or to some flows that are dominated by large-scale magnetic fields such as ion-tori of Rees et al (1982) 11 . But it seems that standard accretion discs are never obese.…”
Section: Discussionmentioning
confidence: 99%
“…In obtaining this conclusion one assumes that accretion flows are stationary and driven by local viscosity. It might not apply to flows forming in TDEs (see e.g., Coughlin & Begelman 2014;Shiokawa et al 2015) or to some flows that are dominated by large-scale magnetic fields such as ion-tori of Rees et al (1982) 11 . But it seems that standard accretion discs are never obese.…”
Section: Discussionmentioning
confidence: 99%
“…Our modeling includes both the effects of inefficient circularization, which simulations have found significantly reduces the accretion rate onto the black hole relative to the fallback rate (Guillochon et al 2014;Shiokawa et al 2015), and limits the luminosity of the disk component to the Eddington limit. We find that the best-fitting circularization time is roughly three times longer than the timescale of peak accretion, resulting in a time of disruption that occurs much earlier than in models in which the viscous effects are neglected; this is the expected behavior for low-mass black holes (M BH ∼10 6 M e ) where circularization takes place at large distances from the black hole (Guillochon et al 2015).…”
Section: Independent Modeling Of the Accretion Rate From X-ray/uv/optmentioning
confidence: 99%
“…Recently, numerical simulations and new analytical work have shown that the development of a TDE light curve is dependent on when the streams of tidal debris intersect each other (Guillochon & Ramirez-Ruiz 2015;Hayasaki, Stone & Loeb 2015;Shiokawa et al 2015). Early interactions appear to be rare and in the majority of cases circularisation occurs late and at a large distance from the BH, 5-10 times further away than predicted by the classical model .…”
Section: A Tidal Disruption Eventmentioning
confidence: 99%
“…In particular we investigate whether the flare could be due to an ac-cretion disc instability, similar to that proposed for flares seen in certain galactic accreting binaries (Cannizzo 1996;Belloni et al 1997a). We also look at recent advances in numerical and analytical modelling of TDE lightcurves (Guillochon & Ramirez-Ruiz 2015;Hayasaki, Stone & Loeb 2015;Shiokawa et al 2015;Piran et al 2015), which show a generally slower rise to peak flux than that predicted by the classical model (Rees 1988).…”
Section: Introductionmentioning
confidence: 99%